Language in the Context of South African Workplace Discrimination Law - Louw, Andre (Potchefstroom Electronic Law Journal, 2022)
This contribution considers the role of language as a prohibited ground of unfair discrimination in the workplace in South Africa, an area of law that has been somewhat neglected in the literature to date. It starts by setting out the constitutional and legislative framework for the protection of language rights and the prohibition of unfair discrimination based on language as a listed ground. It then, with brief comparative reference to other prominent jurisdictions, explains the potential ways in which an employer may unfairly discriminate against employees based on language, following which it considers the potential grounds for justification of language-based discrimination in the workplace. After consideration of the sparse case law on the topic in South Africa, it highlights a few specific issues regarding language and workplace discrimination, before concluding with some thoughts on potential future developments.